PROBLEMATIKA PENDIDIKAN ISLAM DI INDONESIA ABAD 21 - Risda Lestari; Siti Masyithoh (Al-Rabwah, 2023)
Indonesia is a country where the majority of people adhere to Islam. But in reality, in terms of education, Islamic education is not the majority in the position of national education. And Islamic education is seen as always being in a second-row position or a marginal position in the national education system. Whatever education it is, both national education and Islamic education, the essence is to develop human dignity, and humanize humans so that they are truly capable of becoming caliphs. In response to this, Islamic education needs serious attention, especially among scholars and thinkers of Islamic education in Indonesia. Various efforts are needed to restore Islamic education to its former glory. However, there needs to be seriousness in achieving these goals, including seriousness in the management and leadership of reliable Islamic educational institutions. In this article, the author will try to focus on the discussion on the problems of Islamic education in Indonesia in the 21st century, challenges and solutions in responding to these problems of Islamic education. The method used in the preparation of this article is qualitative. Then the approach in this research is by using literature and reference studies in the form of books, journals, articles and scientific papers.